Food and Nutrition Security Strategy 2019 –2023 - EAC (EAC, 2019)
The EAC Agriculture and Food Security Policy and other agricultural sector policies are based on the policies and programs of the Treaty establishing the East African Community (1999) and the EAC Agriculture and Rural Development Policy (EAC-ARDP). Programs and projects for achieving intended objectives are captured in the 25-year (2005-2030) multi-year EAC Agriculture and Rural Development Strategy (EAC-ARDS). These core policy frameworks provided the basis for developing the East African Community Food and Nutrition Security Policy (FNSP) that was adopted by the 7th Sectoral Council on Agriculture and Food Security in September 2014. Also important is the EAC Common Market Protocol (approved in 2010). The EAC Vision 2050 and the EAC 5th Development Strategy, further underscore agriculture as the sector that will drive industrial transformation and economic prosperity in region. The overall goal of the EAC FSNP is “to attain food and nutrition security for all the people of East African Community throughout their life cycle, for their health as well as their social and economic well-being”. With the adoption of the FNSP, EAC Partner States are expected to integrate the policy in their respective national policies and agriculture investment plans to achieve food and nutrition security.
Pages: xvii, 57. Includes Tables and diagrams
Keywords: Food and Nutrition